PENDUKUNG KEPUTUSAN PRIORITAS PEMILIHAN LOKASI PEMASANGAN IKLAN BILLBOARD DI KOTA MEDAN MENGGUNAKAN METODE SMART - Lubis, Imran (Jurnal Sistem Informasi Kaputama (JSIK), 2020)
In the outdoor advertising strategy, the choice of the location of advertising is a major factor because this will determine how effective the range of advertising information displayed is received by the public. Determination of the exact location of billboard advertisements will then support the success of the promotions delivered. In this study using the SMART method so that decision making can be based on multi criteria. This research was conducted to find the best value from each billboard location, then the location sorting process is based on the highest value, which is the priority location for billboard advertisements. The results of this study are made a decision support system to determine the determination of the location of a billboard that is feasible, considered and has not been selected to be selected. Users can input billboard location data, criteria data, sub-criteria data. Then the system will find a solution using the SMART method. After the decision is obtained, the system will display the decision.